ENHANCING PRESCHOOL CHILDREN'S SPEECH DEVELOPMENT THROUGH STEM TECHNOLOGY INTEGRATION (American Journal of Interdisciplinary Research and Development, 2025)
This scientific article explores the potential of Science, Technology, Engineering, and Mathematics (STEM) education in fostering the speech development of preschool children. Speech and language skills are crucial for early childhood development, impacting cognitive, social, and academic outcomes. By integrating STEM technology into preschool curricula, educators can create engaging and interactive learning experiences that promote language acquisition and communication skills. This paper reviews current research on the benefits of STEM education for speech development in young children and provides practical strategies for implementing STEM-based activities in early childhood settings.